PHARMACOECONOMIC ASPECTS OF APIXABAN FOR PREVENTION OF THROMBOEMBOLIC EVENTS IN PATIENTS WITH ATRIAL FIBRILLATION - A. V. Rudakova (Столичная издательская компания, 2015)
For prevention of thromboembolic events in patients with non-valvular atrial fibrillation (NVAF) the following types of antithrombotic therapy are used: anticoagulant therapy with vitamin K antagonists (warfarin), antiplatelet therapy (acetylsalicylic acid) and novel oral anticoagulants such as apixaban, rivaroxaban and dabigatran. Along with clinical efficacy and safety profile one of the main characteristics of any medical technology is economic value and cost-effectiveness. The objective of this review was to describe pharmacoeconomic aspects of using apixaban for stroke and other cardiovascular events prevention in patients with NVAF. Results of the previously published cost-effectiveness studies demonstrated that apixaban was projected to increase life expectancy of the patients with NVAF compared with standards of care warfarin and aspirin, novel oral anticoagulants rivaroxaban and dabigatran. At the same time apixaban is expected to be cost-effective alternative from the Russian Federation national healthcare budget perspective.